Simbol dan Makna Munggah Kap dalam Pembangunan Rumah pada Tradisi Masyarakat Suku Jawa - afta, aftakhul shokhibiyah (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
This study aims to explore the meaning and symbolism of the Munggah Kap tradition in the construction of new houses among the Javanese community in Depok Rejo Village, Trimurjo Subdistrict, Lampung Tengah Regency. Using a qualitative method with an ethnographic approach, data was collected through participatory observation, in-depth interviews, and documentation. The findings show that Munggah Kap holds significant spiritual meaning, where the wood placed at the top of the house symbolizes protection and blessing. Moreover, this tradition strengthens social values such as cooperation and solidarity among residents. The conclusion emphasizes that Munggah Kap not only preserves local cultural identity but also reinforces. The results of the study showed that the types and forms of offerings used were fruits which meant that the results of human labor at work would be presented. And all these traditional offering activities are a manifestation of one's devotion and respect for God and every ritual has a meaning none other than asking for peace and serenity in life.